Hadis tentang Menutup Aurat dalam Bentuk Jibab sebagai Wujud Pendidikan Kesalehan Komunitas Umat Muslim - Pipit Muhibah Waliyah; Teti Ratnasih; Agus Suyadi Raharusun (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about the command to cover the genitals. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the command to cover the genitals in the history of Ahmad No. 19185. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Ahmad No. 19185 is relevant to be used as a proposition for the practice of Islam in carrying out the command to cover the genitals to maintain the spiritual integrity of the Muslim community in the midst of the hijab model trend, so this last point has demanded further research related to the hijab as a function of covering the genitals and the mode of interest of capitalism.